PELATIHAN PENGEMBANGAN BISNIS DIGITAL KUE BASAH BAGI KELOMPOK PKK TINGKAT KELURAHAN KOTA BANDUNG - Herman Hopmans; Said Bambang Nurcahya; Fauzi Caniago (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2022)
The Family Welfare Empowerment Group (PKK) at the kelurahan level has the duties and functions as coaches and implementers of the PKK work program in accordance with the needs of the community in the kelurahan, in addition to planning, gathering, mobilizing potential, also providing guidance and motivation for PKK groups at the RW and RT levels, for that socialization, supervision, monitoring and evaluation of the implementation of the PKK program became very dominant. One of the family welfare empowerment activities is to provide training that aims to increase knowledge and skills in making cakes and marketing digitally (Digital Marketing), Wet Cake is one of the foods most often served at meetings, meetings, picnics, training recitations, as well as community gatherings. Wet cakes themselves are foods that have various food ingredients with soft textures but have a short shelf life, many traditional Indonesian traditional cakes such as lemper, resoles, cucur, kue lumpur, pukis, banana sponge, omelette, and nagasari are put together in a cardboard box and served at the meeting. The tendency of PKK mothers usually to make wet cakes seasonally or if there is a big event so that it cannot be used as a daily business item, for that Digital Marketing is one solution in attracting customers, recognizing customers through digital media is easier to interact because of the content on the account. Social media that is created can see who likes, domicile, economic strata, and community, we can also identify competitors, ask for customer feedback and make survey questionnaires distributed through groups and business communities around the city of Bandung.